A Critical Review on Jeerna Pratishyaya and its Management in Ayurveda (AYUSHDHARA, 2024)
Ayurveda is interminable and ceaseless stream of old pharmaceuticals. The present era is full of stress, chaos, and strain due to lifestyle changes, changes in dietary propensities, urbanisation and industrialisation driving to expanded contamination and increased resistance to the various antibiotics that are responsible for occurrence of several diseases. Nose is one of the sensitive organs in human body which is uncovered to the outside environment, and is more prone to these causative factors leading to recurrent infection. Repeated attacks of Pratishyaya lead to the development of Jeerna Pratishyaya. Numerous treatment modalities are explained in allopathy like corticosteroids, antihistamines, anti-allergies, inhalers etc., but none of them are completely useful in curing the illness as well as preventing its recurrence, besides they have their own side effects. Thus, Ayurvedic management is more advantageous in Jeerna Pratishyaya.